Spatial and Temporal Distribution Characteristics and Causes of Drought in Northwest China Based on SPEI - FENG Shiyuan; CHU Pinging; YAO Xin; YIN Dejun; GUO Yang (Renmin Zhujiang)
Based on monthly precipitation and average temperature data of 113 meteorological stations in Northwest China,through SPEI (standard precipitation evapotranspiration index),this paper analyzes and measures the drought process from 1960 to 2018,discusses the spatial and temporal variation characteristics of drought in Northwest China in recent 60 years combined with M-K test,univariate linear trend analysis and Arcgis software,and studies the drought correlation and periodic characteristics of summer monsoon,ENSO and MEI by using the methods of univariate linear analysis and cross wavelet to find out the causes of drought in Northwest China.The results show that:The multi-timescale SPEI could reflect the drought situation in Northwest China,and the drought intensity increases year by year;The seasonal drought in the study area is obvious,and the drought area increases with the year,especially after 2000s.The drought in eastern Xinjiang,Qinghai and northwest Gansu is extremely serious;SPEI summer drought index has a correlation with East Asian summer monsoon and plateau summer monsoon,and their impact on drought is opposite;The ENSO warm event has a great influence on the drought intensity and frequency before 2000,while after 2000,both ENSO warm and cold events have a great impact on that;The cross-wavelet and wavelet coherence images indicate that SPEI and MEI have similar oscillation period characteristics.There are four periods of high energy,and the resonance period range from 0 to 6 a,indicating that ENSO drives the drought with a period.